If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3x + -8) = 2(12x + 7) Reorder the terms: 8(-8 + 3x) = 2(12x + 7) (-8 * 8 + 3x * 8) = 2(12x + 7) (-64 + 24x) = 2(12x + 7) Reorder the terms: -64 + 24x = 2(7 + 12x) -64 + 24x = (7 * 2 + 12x * 2) -64 + 24x = (14 + 24x) Add '-24x' to each side of the equation. -64 + 24x + -24x = 14 + 24x + -24x Combine like terms: 24x + -24x = 0 -64 + 0 = 14 + 24x + -24x -64 = 14 + 24x + -24x Combine like terms: 24x + -24x = 0 -64 = 14 + 0 -64 = 14 Solving -64 = 14 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 | | -8(3x-4)+1=15 | | 5s+3s=56 |